5 Recent developments in archaeometallurgical research: the Bronze Age Greek Mainland, Crete, and the Cyclades. (November 2022) - Aulsebrook, Stephanie
Abstract : Metallurgy was a fundamental craft industry in the Aegean during the Bronze Age and had some form of impact on almost every aspect of life. This means that archaeometallurgy plays an important role in building our understanding of the region, and has in fact been integrated into Aegean archaeology since the inception of the discipline, well before it was recognized as a separate sub-discipline. Nevertheless, 15 years ago it was still possible for a leading scholar to describe Bronze Age Aegean archaeometallurgy as being in its 'infancy'. Acknowledged weaknesses included a lack of understanding of the Aegean-specific trajectory of metalworking development, reliance on diffusionist theories, a limited interpretative use of scientific analyses, and neglect of research questions tackling social aspects of metal use. This review assesses the progress that has been made since, whether these shortcomings have been addressed, and beneficial future directions for archaeometallurgical studies of the Bronze Age Greek mainland, Crete, and the Cyclades. It focuses on several key themes: the rapidly changing story of Early Aegean metallurgy, the employment of experimental archaeology, the development of scientific techniques and expansion of their use, experimentation with 'big data' approaches, and the varied role of indirect evidence.